Comparative effects of 2 Hz vs. 100 Hz transcutaneous electrical nerve stimulation on upper limb motor function post-stroke: design and rationale for a randomized trial - Song, Chengning; Xie, Huanxin; Lei, Bo; Feng, Nana; Li, Zhixian; Zou, Yanxian (Frontiers in Neurology, 2025)
BackgroundStroke-induced upper limb dysfunction significantly impacts rehabilitation outcomes. Transcutaneous Electrical Nerve Stimulation (TENS) shows promise, but the optimal frequency for motor recovery remains unclear. This study investigates the comparative effects of low-frequency (2 Hz) and high-frequency (100 Hz) TENS in post-stroke upper limb rehabilitation. This article describes the design and conduct of this trial.Method/designAn assessor-blinded, single-center randomized controlled trial with partial participant blinding (active vs. placebo) will recruit 156 participants aged 40–80 years, 10 days to 2 months post-stroke, with mild-to-moderate upper-limb impairment (Brunnstrom III–V). Participants will be randomly assigned (1:1:1:1) to 2 Hz TENS, 100 Hz TENS, placebo TENS, or a no-TENS usual-care control for 8 weeks (3 sessions/week, 30 minutes/session). The primary outcome is the Fugl–Meyer Assessment of the Upper Extremity (FMA-UE). Secondary outcomes include Manual Muscle Testing (MMT), the Modified Ashworth Scale, electroencephalography (EEG) metrics, the Lindmark Motor Score (hand subscale), and the Barthel Index, assessed at baseline, weeks 4 and 8, and at 1 and 3 months post-intervention.DiscussionThis trial is, to our knowledge, among the first randomized head-to-head comparisons of low- vs. high-frequency TENS for post-stroke upper-limb rehabilitation. Its findings are expected to clarify frequency-dependent effects, narrow the plausible range of effective parameters, and provide evidence to inform clinical guidelines and future rehabilitation strategies.